Metabolic syndrome in obese versus non-obese persons In basrah - Ajlan, Salman K. (AL-Kindy College Medical Journal, 2012)
Background: The prevalence of obesity is continuously rising world-wide. Obesity is an important risk factor of cardiovascular disease (CVD), metabolic syndrome (MS), and type 2 diabetes (T2D). Objective: To estimate the frequency of MS in obese versus non-obese subjects in Basrah, Iraq . Methods: This is a prospective clinical study performed in Al-Sadr Teaching Hospital, Basrah, and included 86 obese subjects (with a BMI ≥ 30), 39 males and 47 females, and 132 non-obese subjects ( with a BMI < 30 ), 60 males and 73 females as a control group. Measurement of height, weight, waist circumference (WC), blood pressure ( BP ), fasting blood glucose ( FBG ), total cholesterol (TC), triglycerides (TG ) and high density lipoprotein- cholesterol (HDL-C) levels were carried out. The updated US National Cholesterol Education Program Adult Treatment Panel III ( updated NCEP ATP III ) definition was used for the diagnosis of MS. Results: The frequencies of MS were significantly higher among obese male and female persons (38.5% and 42.6% respectively) compared to non-obese male and female persons (15.0% and 19.4% respectively), (P<0.01). On the other hand, the frequencies of MS were non-significantly higher among over weight male and female subjects (19.2% and 24.3% respectively) compared to normal weight male and female subjects (11.8% and 14.3% respectively), (P>0.05). The major determinants for MS in obese persons in either sex were WC, BP and TG ( P<0.001, P<0.001 and P<0.05 respectively). Conclusions: Obese individuals are at a substantial risk for MS, and thereby, at a high risk of atherosclerotic CVD and T2D, and their complications.